Linear Independence of Logarithms of Cyclotomic Numbers and a Conjecture of Livingston. Issue 1 (12th March 2020) - Chatterjee, Tapas; Dhillon, Sonika
Abstract: In 1965, A. Livingston conjectured the $\overline{\mathbb{Q}}$ -linear independence of logarithms of values of the sine function at rational arguments. In 2016, S. Pathak disproved the conjecture. In this article, we give a new proof of Livingston's conjecture using some fundamental trigonometric identities. Moreover, we show that a stronger version of her theorem is true. In fact, we modify this conjecture by introducing a co-primality condition, and in that case we provide the necessary and sufficient conditions for the conjecture to be true. Finally, we identify a maximal linearly independent subset of the numbers considered in Livingston's conjecture.